Easing the rules of health protocols: A critical discourse analysis of Indonesian president’s speech on Covid-19 handling in 2022 - Liando, Nihta V. F.; Tatipang, Devilito Prasetyo; Rorimpandey, Rinny; Karisi, Yofri (Universitas Islam Negeri Banda Aceh, 2022)
The president is the icon of the number one person in a country, and the position of president is the highest position that allows him to always communicate with the public, namely making public speeches. The understanding of the listeners or the public towards the speech delivered by the president allows misunderstandings to arise in interpreting the meaning it contains, both implied and expressed. Therefore, it is very necessary to have a critical discourse analysis of what the president conveys in general. For this reason, the purpose of this research is to analyze the macro structure, superstructure, and micro structure contained in the text of the president's speech, as well as to reveal the implied intent of the president who put forward a statement in relation to action, context, history, power, and ideology. In addition, because the essence of the research is to describe in detail, the method used is qualitative with the principle of critical discourse analysis from Van Djik. Furthermore, the speech delivered by President Joko Widodo, which was delivered online on the metrotvnews youtube channel on May 19, 2022, was used as the object of this research. By applying the techniques of documentation, observation, systematic recording, literature study and listening to the data and research objects, the results show that the researcher found three dimensions of critical discourse analysis in speech texts, namely macro structure, supra structure, and micro structure. The characteristics of critical discourse analysis found in news texts are action, context, history, power, and ideology. In addition, five implied intentions were also found in the video that was shown online